A multifunctional ratiometric electrochemical sensor for combined determination of indole-3-acetic acid and salicylic acid. Issue 6 (17th January 2020) - Hu, Ye; Wang, Xiaodong; Wang, Cheng; Hou, Peichen; Dong, Hongtu; Luo, Bin; Li, Aixue
Abstract : For the first time, a multifunctional ratiometric electrochemical sensor was developed for quantifying IAA and SA simultaneously. Abstract : Indole-3-acetic acid (IAA) and salicylic acid (SA) are two important phytohormones. In this work, for the first time, a ratiometric electrochemical sensor was developed for quantifying IAA and SA simultaneously. A composite of multi wall carbon nanotubes (MWNT) and carbon black (CB) was used to enhance the sensitivity of electrochemical detection. Ferrocene (Fc) was used as the reference molecule to offer a built-in correction to improve the accuracy. A good linearity was constructed between the I IAA / I Fc and the concentration of IAA from 25 μM to 1000 μM. The linear equation was y = 0.00159 x + 0.124 ( R 2 = 0.9887). The LOD for IAA was 1.99 μM. Meanwhile, the I SA / I Fc gradually increased with increasing concentration of SA. The linear regression equation for SA was y = 0.00107 x + 0.34465 ( R 2 = 0.9488) with the LOD of 3.30 μM. Thus, the as-prepared multifunctional ratiometric electrochemical sensor was successfully applied to detect IAA and SA at the same time. This sensor was also successfully used to detect IAA and SA in the homogenates of soybean seedlings under salt stress, confirming the practical applicability of the sensor. And the obtained results agreed well with those obtained by the ultra performance liquid chromatography-mass spectrometry (UPLC-MS) method.